ALIH FUNGSI LAHAN PERTANIAN DI KABUPATEN MINAHASA UTARA - Yuniarti Amelhia Lapatandau; Grace A. J. Rumagit; Caroline B.D. Pakasi (Sam Ratulangi University, 2017)
This study aims to find out how the conversion of agricultural land in 2013 to 2016 in North Minahasa District. The study was conducted from February to June 2017. The data used were secondary data obtained from North Minahasa National Land Agency (BPN) and Central Bureau of Statistics (BPS) of North Sulawesi. Data analysis used is descriptive data analysis method by using tables and graphs to describe conversion of agricultural land in Kabupaten Minahasa Utara. Analysis of the data taken is expert report of agricultural land function in North Minahasa District from 2013 to 2016. The results show that land conversion in North Minahasa District from 2013 to 2016 tends to increase. With increasing of farming land conversion means increasingly narrow agricultural land, while land conversion increases.